2022
DOI: 10.1590/fst.22922
|View full text |Cite
|
Sign up to set email alerts
|

Fermented beverage obtained from soy and rice incorporated with inulin and oligosaccharides derived from succinoglycan

Abstract: The aim of this study was to evaluate the effect of incorporating inulin and oligosaccharides resulted from the enzymatic hydrolysis of the commercial succinoglycan, regarding the physicochemical properties, rheology, syneresis and probiotic viability of soy and rice-based fermented beverages added with Lactobacillus paracasei. Four formulations were prepared and supplemented with 3.5% of inulin; 0.5% of succinoglycan oligosaccharides; 3.0% of inulin and 0.5% of succinoglycan oligosaccharides, and evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In another study, the effect of the incorporation of inulin and succinoglycan oligosaccharides on the physicochemical properties, rheology, syneresis and probiotic viability of soy and rice fermented beverages with Lactobacillus paracasei was evaluated. It was found that these formulations improved the digestibility of the protein, reduced syneresis and maintained probiotic viability after being exposed to intestinal resistance tests [100]. In another recent assay, the taste-related metabolites, volatile compounds, and amino acids were examined in a traditional glutinous rice fermented beverage supplemented with chestnuts as a fermentation substrate for LAB.…”
Section: Rhizopus Oryzaementioning
confidence: 99%
“…In another study, the effect of the incorporation of inulin and succinoglycan oligosaccharides on the physicochemical properties, rheology, syneresis and probiotic viability of soy and rice fermented beverages with Lactobacillus paracasei was evaluated. It was found that these formulations improved the digestibility of the protein, reduced syneresis and maintained probiotic viability after being exposed to intestinal resistance tests [100]. In another recent assay, the taste-related metabolites, volatile compounds, and amino acids were examined in a traditional glutinous rice fermented beverage supplemented with chestnuts as a fermentation substrate for LAB.…”
Section: Rhizopus Oryzaementioning
confidence: 99%
“…An interesting possibility is to use succinoglycan as a fat substitute in ice cream and mayonnaise. Recently, research has shown that succinoglycan in the form of oligosaccharides was incorporated into fermented soy and rice-based beverages, bringing food alternatives to groups of individuals who have dietary restrictions (Nascimento et al, 2022). Due to the potential applicability of exopolysaccharides (Moyib et al, 2019), especially succinoglycan, in recent years several renewable carbon sources have been investigated for the production of bacterial biopolymers, aiming to produce biomaterials with lower environmental impact, higher performance, better applicability and lower production cost (Andhare et al, 2017b;Moosavi-Nasab et al, 2012).…”
Section: Introductionmentioning
confidence: 99%